Starters and non-starters soccer players in competition: is physical performance increased by the substitutions? - Alfonso Castillo-Rodríguez; José Luis González-Téllez; Antonio Figueiredo; José Luis Chinchilla-Minguet; Wanesa Onetti-Onetti (BMC, 2023)
Abstract Background Non-starters soccer players have a great role within the team, being indispensable to reduce fatigue, as well as to maintain and increase the team's performance during the match. Objective This study aimed to analyze the physical performance of the starter and non-starters players during competitive soccer matches. Methods Twenty-two soccer players participated in this study, divided into two groups according to the role in the match (starters or non-starters). WIMU Global Positioning System devices were used in order to record physical performance metrics. Independent samples t-test and one-way ANOVA tests were performed to compare starters and non-starters, and the playing position, respectively, and two-way ANOVA test was perform with these factors too. Results There were no differences in the main physical performance metrics between starters and non-starters players during competition, although there were differences in physical performance metrics according to the playing position. Midfielders performed highest distance per minute, player load, and distance covered between 12 and 21 km·h− 1 (p < .05). Finally, distance covered at speeds greater than 24 km·h− 1 was predicted by the playing role (starters and non-starters) and playing position factors with 88% of explained variance (η p 2  = 0.772). Conclusion The main findings of this study showed that non-starter players had a similar physical performance during competitive matches as the starter players for whom they are substituted. In addition, the playing position determined different physical performance, contributing in this manuscript that behavior and decision-making of the players could be affected by their position in the field. More studies are needed on non-starter player performance and contextual factors that could influence the physical responses of these players.